Mengayau Entertainment / Mohd Sadam Abd Latif... [et al.] - Abd Latif, Mohd Sadam; Salsidu, Muhammad Khairuddin; Taibin, Kerry; Abdullah, Mohd Azren (2013)
The name of our company is MENGAYAU ENTERTAINMENT . The business is in form of Private Limited which consists of four members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is providing mobile stage which consist of entertainment and suitable for all ages. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Mohd Sadam Bin Abd Latif as the General Manager and Marketing manager, Muhammad Khairuddin Bin Salsidu as the Administration Manager, Mohd Azren Abdullah as the Operational Manager, Kerry Taibin as the Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills an d ability. The management team will be led by the General Manager and assist by the other executives. The General Manager is responsible in planning, leading, controlling and organizing the business. The Administration Executive is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. The Operational Executive is responsible to the entire job that related to the operation and will supervise and coordinate the operation of the business. The Marketing Executive will responsible to create the marketing plan, identifying the customer's need and demand, identifying the competitors, target market, market size and forecast the future market. Lastly, the Financial Executive will handle the financial matters such as preparing the budget and financial statement for expenses of each departments and controlling the flow of the money of the organization.